Major Pigment and Fragrant Compounds in Selected Orchids and the Correlation between Phenylalanine Ammonia Lyase (Ec 4.3.1.5) Activity and Anthocyanin Content - Mohamad Azzeme, Azzreena (2009)
Orchidaceae family has become one of the important commercial commodities in agricultural industry worldwide, either as potted plants or as cut flowers due to the attractive colour produced in flower petals. However, the colour of the orchid flowers usually found to be non-patterned and non-uniformed between the species or in a single orchid plant. The major pigment synthesized in the orchid flower is commonly derived from anthocyanin family. Therefore, determining the distribution and characteristics of the key enzyme of phenylpropanoid pathway (phenylalanine ammonia lyase; PAL) in different orchid tissues and its correlation to anthocyanin content were the main objective in this study. Apart from that, the major fragrant compounds were also determined by using gas chromatography-mass spectrometry (GC-MS). Results obtained from the studies revealed that anthocyanins content were found to be the highest when compare to β-carotenes and chlorophylls in coloured orchid petals (Dendrobium Sonia 17, Vanda Mimi Palmer, Phalaenopsis bellina and Oncidium Sharry Baby) at a range of 0.07 to 0.95 mg/g fresh weight. For non-anthocyanin containing orchids (D. Savin White, P. bellina var. alba and V. White (V. Velthuis x Coeletis alba)), the highest pigment content present in their petals was chlorophyll at a range of 0.05 to 0.34 mg/g fresh weight. Anthocyanin and β-carotene pigment were not detected in in vitro orchid seedlings, protocorm-like bodies (PLBs) and leaves. The major pigment found to be present in in vitro seedlings, PLBs and leaves of orchids was chlorophyll at a range 0.05 to 0.34 mg/g fresh weight. The total β-carotene content was determined to be highest in O. Taka petals (0.09 ± 0.01 mg/g fresh weight). Additionally, the major anthocyanidin pigment in orchid flowers was analyzed using thin layer chromatography (TLC) and high performance liquid chromatography (HPLC). Malvidin (0.113 ± 0.00 mg/g fresh weight) and petunidin (0.117 ± 0.00 mg/g fresh weight) were present in D. Sonia 17 petals, while, petunidin (0.109 ± 0.00 mg/g fresh weight) and delphinidin (0.096 ± 0.00 mg/g fresh weight) were observed in P. bellina. Only delphinidin was detected in V. Mimi Palmer (0.129 ± 0.02 mg/g fresh weight) and O. Sharry Baby (0.08 ± 0.02 mg/g fresh wight) petals. Besides, the major fragrant compounds was also determined in fragrant orchids (V. Mimi Palmer, P. bellina, P. bellina var. alba and O. Sharry Baby). A study was also carried out to determine the correlation of PAL activity and anthocyanin content in orchid flowers. PAL is the first enzyme involved in anthocyanin biosynthesis. Its activity was found to be positively correlated with the total anthocyanin content in the coloured orchid petals. The PAL activity and total anthocyanin content in the full bloomed of coloured orchid flowers was at a range 0.12 to 0.36 nmol/min/mg protein and 0.07 to 0.95 mg/g fresh weight, respectively. Apart from that, from the Pearson correlation analysis, PAL activity was found to be significant positive correlated with the anthocyanin content during the development of flower of D. Sonia 17, V. Mimi Palmer, P. bellina and O. Sharry Baby (r=0.989, p<0.05; r=0.867, p<0.05; r=0.989, p<0.05 and r=0.966, p<0.05, respectively). Therefore, higher PAL activity is associated with higher anthocyanin content in petals of coloured orchids. In a subsequent study on characterization of PAL, it was observed that PAL from orchid flower, seedlings, PLBs and leaves showed similar optimum pH (pH 8.5), temperature (30 °C) and incubation time (15 min) among each other. However, PAL was found to have different Vmax and Km values towards L-phenylalanine as its substrate. The Km and Vmax values of PAL towards L-phenylalanine were found within a range of 100 to 264 μM and 0.32 to 0.98 μmol/min.mg protein, respectively. Besides, PAL was also activated by the addition of Mg2+, Mn2+ and Ca2+ ions in its reaction mixture.